Using more than 801 296 small‐molecule crystal structures to aid in protein structure refinement and analysis. Issue 3 (1st March 2017) - Cole, Jason C.; Giangreco, Ilenia; Groom, Colin R.
Abstract : A guide to how the Cambridge Structural Database can be used to aid macromolecular crystallography. Abstract : The Cambridge Structural Database (CSD) is the worldwide resource for the dissemination of all published three‐dimensional structures of small‐molecule organic and metal–organic compounds. This paper briefly describes how this collection of crystal structures can be used en masse in the context of macromolecular crystallography. Examples highlight how the CSD and associated software aid protein–ligand complex validation, and show how the CSD could be further used in the generation of geometrical restraints for protein structure refinement.